"The Price you Pay": The Impact of State-Funded Secondary School Performance on Residential Property Values in England - Glen, John; Nellis, Joseph G. (Economists' Association of Vojvodina, 2010)
This paper examines the relationship between state-funded secondary school performance and local residential property values in seven major English cities. When choosing which secondary school they wish their children to attend, parents will be aware of the school's performance in Key Stage 3, GCSE and A- level examinations. We suggest that GCSE examination results will be the measure of school performance that parental choice will be most closely correlated with. Therefore, secondary schools with good GCSE examination results will be "oversubscribed" in that more students will wish to attend these schools than there are places available. Schools will then have to develop mechanisms for rationing the available places - central to rationing strategies in English schools at the moment is geographical proximity of the family home to the school of choice. Parents will thus have a strong incentive to purchase houses in the "catchment" area of high performing schools. Our results suggest that this is the case, with high performing schools stimulating a price premium in local residential property markets of between 1% and 3% for each additional 10% point improvement in the pass rate in GCSE examinations.